2020
DOI: 10.1002/marc.202000288
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Addition–Fragmentation Reactions to Produce Low Dispersity Poly(isobornyl acrylate) and Blocky Copolymers by Semibatch Radical Polymerization

Abstract: Solution radical homopolymerization of isobornyl acrylate (iBoA) under starved‐feed higher temperature conditions unexpectedly leads to polymer product with low dispersity (<1.3) compared to the polymerization of butyl acrylate (BA) under identical conditions. Both backbiting and β‐scission reactions occur, as the poly(iBoA) product contains close to 100% terminal double bond (TDB) functionality. However, the addition of monomer to the midchain radicals formed by backbiting is sterically hindered, greatly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[ 32 ] t‐BuAAm backbiting is expected since the SP‐PLP‐EPR study by Kattner and Buback conclusively showed that MCR radicals form in the AAm system, [ 26 ] and since the mechanism has been shown to occur with all acrylate monomers irrespective of the ester group structure. [ 28,45 ] The reduced rate of monomer conversion that occurs as w mon , 0 is decreased from 0.20 and 0.10 (Figure 1a) provides strong evidence of t‐BuAAm backbiting, and omitting the reaction from the model resulted in systematic overprediction of the experimental batch conversion profiles under conditions for which the influence of backbiting is increased (i.e., at higher temperature and reduced w mon , 0 ). Thus, the kbbtBuAAm$k_{{\rm{bb}}}^{{\rm{t - BuAAm}}}$ values were fitted to batch conversion profiles at 60 °C and 70 °C, while assuming that the activation energy for the reaction is the same as reported for AAm.…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 ] t‐BuAAm backbiting is expected since the SP‐PLP‐EPR study by Kattner and Buback conclusively showed that MCR radicals form in the AAm system, [ 26 ] and since the mechanism has been shown to occur with all acrylate monomers irrespective of the ester group structure. [ 28,45 ] The reduced rate of monomer conversion that occurs as w mon , 0 is decreased from 0.20 and 0.10 (Figure 1a) provides strong evidence of t‐BuAAm backbiting, and omitting the reaction from the model resulted in systematic overprediction of the experimental batch conversion profiles under conditions for which the influence of backbiting is increased (i.e., at higher temperature and reduced w mon , 0 ). Thus, the kbbtBuAAm$k_{{\rm{bb}}}^{{\rm{t - BuAAm}}}$ values were fitted to batch conversion profiles at 60 °C and 70 °C, while assuming that the activation energy for the reaction is the same as reported for AAm.…”
Section: Resultsmentioning
confidence: 99%
“…, backbiting), (ii) βC-scission reactions and (iii) intermolecular chain transfer. 29–31 Notably, backbiting and βC-scission side reactions can slow down the polymerization process, shortening the length of the main chain and producing macromonomers. However, the electron paramagnetic resonance (EPR) measurements have revealed that these reactions are expected to become important at elevated temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, one should bear in mind that FRP of IBA similar to other acrylate monomers, might often be accompanied by the occurrence of unwanted side reactions such as (i) intramolecular chain transfer (i.e., backbiting), (ii) βC-scission reactions and (iii) intermolecular chain transfer. [29][30][31] Notably, backbiting and βC-scission side reactions can slow down the polymerization process, shortening the length of the main chain and producing macromonomers. However, the electron paramagnetic resonance (EPR) measurements have revealed that these reactions are expected to become important at elevated temperatures.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
“…The U% was combined with the DP n determined by SEC analysis to estimate the percentage of chains that contain a TDB. [12] 13 C NMR was conducted using a 500 MHz Bruker Avance NEO spectrometer at room temperature. The samples were prepared by dissolving the dried polymer in CDCl 3 to ≈20 wt.% polymer.…”
Section: Methodsmentioning
confidence: 99%